Relationship Between Infrastructure and Facilities for Students Preparedness to Deal with The Tsunami - Sujarwo Sujarwo; Noorhamdani Noorhamdani; Mukhamad Fathony (Universitas Medan Area, 2018)
ABSTRAKSarana prasarana merupakan aspek penting di dalam manajemen bencana, terutama wilayah yang memiliki potensi tsunami yang tinggi seperti kepulauan Mentawai. Salah satu kelompok yang rentan terhadap bencana tsunami adalah siswa sekolah. Kerentanan ini dikarenakan masih rendahnya kesiapsiagaan siswa SSB dalam pengurangan risiko bencana di sekolah. Penelitian ini bertujuan untuk menganalisis hubungan sarana prasarana terhadap kesiapsiagaan siswa SSB dalam pengurangan risiko bencana tsunami. Penelitian ini adalah penelitian kuantitatif, dengan menggunakan desain observational analitik korelatif dan pendekatan cross sectional dengan sampel sebanyak 109 siswa yang di ambil dari kelas 5 dan 6 di 3 SDN yaitu SDN 13, SDN 16 dan SDN 17 di Kecamatan Sipora Kabupaten Kepulauan Mentawai. Terdapat hubungan yang signifikan antara sarana prasarana dengan kesiapsiagaan siswa SSB dalam pengurangan risiko bencana tsunami, dengan nilai (p=0.000) dan nilai r =0.98. Sarana prasarana memiliki hubungan yang signifikan dengan kesiapsiagaan siswa SSB sehingga dapat menghambat kesiapsiagaan siswa dalam pengurangan risiko bencana tsunami di Kecamatan Sipora Kabupaten Kepulauan Mentawai.Kata Kunci: Sarana Prasarana, Kesiapsiagaan, Pengurangan Risiko Bencana ABSTRACTInfrastructure and facilities is an important aspect of disaster management especially in areas with high Tsunami potential such as Mentawai Islands. One of the groups which are vulnerable to Tsunami is students. This vulnerability is due to the low preparedness of Sekolah Siaga Bencana (School-Based Disaster Preparedness, abbreviated as SBB) students in disaster risk reduction. This study aims to analyze the relationship of infrastructure and facilities to the preparedness of SSB students in disaster risk reduction especially tsunami. This study is a quantitative research conducted by using a correlative-analytic observational design and cross-sectional approach with a sample of 109 students taken from 5th and 6th grader in 3 Sekolah Dasar Negeri (Elementary School or SDN) namely SDN 13, SDN 16 and SDN 17 in Sipora District, Mentawai Islands. There is a significant relationship between infrastructure-facilities and the preparedness of SBB students towards the reduction of Tsunami risk with the value of (p = 0.000) and r = 0.98. Infrastructure and facilities have a significant relationship with the preparedness of SBB students so that it can inhibit the reduction of tsunami risk in Sipora District, Mentawai Islands.Keywords: Infrastructure and facilities, Preparedness, Disaster Risk Reduction